First report on the metabolic characterization of Sterigmatocystin production by select Aspergillus species from the Nidulantes section in Foeniculum vulgare - Mahata, Pranab Kumar; Dass, Regina Sharmila; Gunti, Lokanadhan; Thorat, Pooja Appasaheb (Frontiers in Microbiology, 2022)
ABSTRACT Spices are typically grown in climates that support the growth of toxigenic fungi and the production of mycotoxins. The Aspergilli described in this study, as well as the sterigmatocystin (STC) detected, are causes for concern due to their potential to induce food poisoning. One of the most well-known producers of the carcinogenic STC is Aspergillus nidulans. This research explores the occurrence of STC-producing fungi in Foeniculum vulgare, a spice that is marketed in India and other parts of the world. This innovative study details the mycotoxigenic potential of five Aspergilli belonging to Section Nidulantes, namely Aspergillus latus (02 isolates), Emericella quadrilineata (02 isolates), and Aspergillus nidulans (01 isolate), with respect to STC contamination. These five isolates of Aspergilli were screened to produce STC on yeast extract sucrose (YES) medium in a controlled environment with regard to light, temperature, pH, and humidity, amongst other variables. The expression patterns of regulatory genes including aflR, laeA, pacC, fluG, flbA, pksA, and mtfA were studied on czapek dox agar (CDA) medium. STC biosynthesis by the test isolates was done in potato dextrose broth (PDB) under optimum conditions, followed by extraction and purification of the broth using ethyl acetate. High-Performance Liquid Chromatography (HPLC) with an ultraviolet (UV) detector was utilized to detect compounds in eluted samples. F. vulgare contains Aspergilli that have been shown to have mycotoxigenic potential, which can accumulate in the spice during its active growth and thereby cause elaboration of mycotoxins. Aspergillus, food spoilage, HPLC, mycotoxigenic, mycotoxin, regulatory genes